2006
DOI: 10.3354/meps310047
|View full text |Cite
|
Sign up to set email alerts
|

Cross-community congruence of patterns in a marine ecosystem: Do the parts reflect the whole?

Abstract: Cross-community congruence patterns of species diversity metrics and community similarity between macrobenthic infauna, epibenthic megafauna, demersal fish and microzooplankton ciliates were studied in 6 areas in the Eastern Mediterranean. These species-rich communities, cooccurring in space and time, were intensively sampled during 2 cruises, in seasons reflecting different levels of subtle anthropogenic stress. Comparisons of patterns showed high positive correlation of similarities in community structure be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…First, we examined the efficacy of biological surrogacy for measuring compositional turnover rather than the more traditional measures of species richness. Second, in addition to comparing congruency patterns between assemblages in pointlocation biodiversity data (as presented in many marine studies to date; Beger et al 2003, Karakassis et al 2006, Sutcliffe et al 2012), we used point-location data combined with environmental data to model and predict spatially explicit turnover patterns. The consistency of the relationships between compositional turnover and environmental covariates for the fish, invertebrate, and macroalgal communities, and the resulting congruency in predicted biodiversity patterns, suggest that where the goal is broadscale prediction of biodiversity, data collection on only one taxonomic group will provide good representation of the biodiversity of other taxa.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined the efficacy of biological surrogacy for measuring compositional turnover rather than the more traditional measures of species richness. Second, in addition to comparing congruency patterns between assemblages in pointlocation biodiversity data (as presented in many marine studies to date; Beger et al 2003, Karakassis et al 2006, Sutcliffe et al 2012), we used point-location data combined with environmental data to model and predict spatially explicit turnover patterns. The consistency of the relationships between compositional turnover and environmental covariates for the fish, invertebrate, and macroalgal communities, and the resulting congruency in predicted biodiversity patterns, suggest that where the goal is broadscale prediction of biodiversity, data collection on only one taxonomic group will provide good representation of the biodiversity of other taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Latitudinal patterns have been less clear, but, in general, diversity of benthic communities or of component groups has been shown to decline with increasing latitude in the northern hemisphere (Rex et al 1993, Boucher & Lambshead 1995, Culver & Buzas 2000, Mokievsky & Azovsky 2002, Hillebrand 2004, Witman et al 2004, Renaud et al 2006. Other regional studies, however, have failed to detect this pattern or even showed regionally opposite trends (Heip et al 1992, Kendall & Aschan 1993, Dauvin et al 1994, Kendall 1996, Clarke & Lidgard 2000, Lambshead et al 2000, Ellingsen & Gray 2002, Rees et al 2007, and patterns in some taxonomic or trophic groups are not replicated in others (Azovsky 2000, Ellingsen 2001, Hillebrand 2004, Karakassis et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Karakassis et al . () found high positive correlation of similarities in community structure between macrofauna and megafauna and megafauna and fish, but low or even negative correlations for diversity. While our correlations were generally low, the highest correlations were frequently negative, the opposite of that required for a surrogate.…”
Section: Discussionmentioning
confidence: 95%
“…The lack of congruence between diversity patterns of demersal fish and epibenthos found in this study is consistent with other studies. While a number of studies have observed relationships between fish community composition and either epifaunal or infaunal communities (Karakassis et al ., ; Sell & Kröncke, ) or habitats (Kostylev & Hannah, ; Fisher et al ., ), the same is not true for diversity comparisons. Karakassis et al .…”
Section: Discussionmentioning
confidence: 99%